A Study of Grief From Farm Loss - Graham, Marie; Henjum, Ray; Freeze, Rick (Canadian Journal of Counselling and Psychotherapy, 2011)
A survey of 16 rural families who had suffered the loss of their family farms in the Brandon, Manitoba, area was done to detect the presence of grief from farm loss. More intensive interviews of six of these families also were conducted. The presence of grief in these unfortunate families was found. The characteristics of farm loss included: leaving the farm, losing the home, losing the property of others, leaving the community, and emotional affects. The strongest emotional affects reported were: sadness, pining, tension, anger, loneliness, anxiety, and shock. In addition, subjects reported having increased difficulty in social relationships and in organizing their lives. The implications of these findings are discussed and counselling suggestions are made. Counsellors who would help farm loss families to relocate and to launch new Iifecareers must be prepared to help them to work through their grief process.